2012
DOI: 10.1371/journal.pone.0048269
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Molecular Methods for Early Detection and Serotyping of Enteroviruses in Throat Swabs of Pediatric Patients

Abstract: BackgroundEnteroviruses include over 100 serotypes and usually cause self-limited infections with non-specific symptoms in children, with the exceptions of polioviruses and enterovirus 71 which frequently cause neurologic complications. Therefore, early detection and serotyping of enteroviruses are critical in clinical management and disease surveillance. Traditional methods for detection and serotyping of enteroviruses are virus isolation and immunofluorescence assay, which are time-consuming. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…As expected, detection rate of the VI-IFA was lower than that of the VP1-CODEHOP test (48% vs. 58%). After verification with the serotype-specific serum neutralization tests, we further confirmed high accuracy of the VP1-CODEHOP test, which is consistent with a previous study with a small sample size [8]. The previous study is a pilot study and included 110 cases for comparing two molecular methods (5'-UTR and VP1-CODEHOP) and the traditional method (virus isolation).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…As expected, detection rate of the VI-IFA was lower than that of the VP1-CODEHOP test (48% vs. 58%). After verification with the serotype-specific serum neutralization tests, we further confirmed high accuracy of the VP1-CODEHOP test, which is consistent with a previous study with a small sample size [8]. The previous study is a pilot study and included 110 cases for comparing two molecular methods (5'-UTR and VP1-CODEHOP) and the traditional method (virus isolation).…”
Section: Discussionsupporting
confidence: 87%
“…Based on the VP1-CODEHOP test, we found that multiple EV71 genotypes co-circulated in 2008–2012 but EV71 sub-genotypes B5b and B5c caused large-scale epidemics in 2008 and 2012, respectively, which are consistent with other studies analyzing full VP1 sequences and complete genomes [24, 27]. Although a degenerate primer set targeting conserved region of enteroviruses (5’-UTR) had been widely used on molecular diagnostic systems, the 5’-UTR-based molecular diagnosis cannot precisely identify serotypes of human enteroviruses [8, 28]. …”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Molecular methods such as polymerase chain reaction (e.g. nested PCR) are also used for the detection of viral ribonucleic acid [8]. Although these tests possess increased sensitivities in CSF and blood specimens, their utility is limited to the viremia phase of the infection (usually over a few days).…”
Section: Introductionmentioning
confidence: 99%